Accused : a Rosato & Associates novel - Scottoline, Lisa. (New York : St. Martin's Press, 2013)
Thirteen year old Allegra Gardner believes that the imprisoned Lonnie did not kill her sister six years ago. Taking on the case seems foolhardy to Mary DiNunzio, because the Gardner family is wealthy and powerful and Allegra's parents do not believe in reopening the case. But the Rosato & Associates firm can never resist an underdog.
Keywords: Rosato & Associates (Imaginary organization) -- Fiction; Women lawyers -- Fiction; Murder -- Investigation -- Fiction; False imprisonment -- Fiction; Suspense fiction; Legal stories; Mystery fiction